Penetapan Lokasi dalam Pengadaan Tanah Skala Kecil bagi Pembangunan untuk Kepentingan Umum - Andi Besse Tenri Adjeng; Aminuddin Salle; Farida Patittingi (Perspektif Hukum, 2017)
Small-scale land acquisition is an activity of providing land by giving fair and fair compensation to the entitled parties. The land area for small-scale land is not more than 5 hectares. This study aims to identify and analyze the implementation of small-scale land acquisition by using the stages of determining the location and analyzing and finding legal implications for land acquisition by using location determining stages. This type of research is an empirical law study in which research serves to see the law in a real sense and examines how the workings of the law in the environment. Data are analyzed qualitatively that is decomposition, depiction, and explanation of certain circumstances, processes or events. The results of the study indicate that the implementation of small-scale land acquisition by using location determination in East Java is through 4 (four) stages of planning, preparation, implementation, delivery of results based on the Decree of Governor of East Java. The decree is inconsistent with the provisions of Article 121 paragraph (3) of Presidential Decree Number 148 of 2015. The legal implications of this investigation are not null and void, but it can only be revoked if a party sues them.